-3m-8-(2m-5)=-15-5m

Simple and best practice solution for -3m-8-(2m-5)=-15-5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3m-8-(2m-5)=-15-5m equation:


Simplifying
-3m + -8 + -1(2m + -5) = -15 + -5m

Reorder the terms:
-3m + -8 + -1(-5 + 2m) = -15 + -5m
-3m + -8 + (-5 * -1 + 2m * -1) = -15 + -5m
-3m + -8 + (5 + -2m) = -15 + -5m

Reorder the terms:
-8 + 5 + -3m + -2m = -15 + -5m

Combine like terms: -8 + 5 = -3
-3 + -3m + -2m = -15 + -5m

Combine like terms: -3m + -2m = -5m
-3 + -5m = -15 + -5m

Add '5m' to each side of the equation.
-3 + -5m + 5m = -15 + -5m + 5m

Combine like terms: -5m + 5m = 0
-3 + 0 = -15 + -5m + 5m
-3 = -15 + -5m + 5m

Combine like terms: -5m + 5m = 0
-3 = -15 + 0
-3 = -15

Solving
-3 = -15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4y+3(4y+4)=-4-9(4-y) | | 2a-3b=465 | | 3(3x-7)+2(5x+9)=0 | | X/2-x/11=9 | | 2(x-5)+4=5x-3(2+x) | | x+17-4=3+y | | x/6=4=15 | | 8(x-5)+9=8x+2 | | c=17v | | 11x+4y=17 | | 2x+3=2(x+1)1 | | -2x+3x=10 | | -1+15x=15x-1 | | 4x^4y^4+-2xy^2=0 | | 3n-10=21 | | 0=-16t^2+12.51t | | 6000=(40+x)+(40+x)+x+x | | 18b^2+25b-3= | | 10=2(u-5)-6u | | 1474x+4=20 | | 6000=(40+x)(x) | | 0.2(x+60)-0.08(x-30)=8.4 | | 12x+6=8x+42 | | 1/6x-2/7=4/7 | | f(x)=x^2+7x-7 | | (2x+1)(9x+b)=6x^2-5x+c | | 7.93-15.29v=0.66v | | 77=.5(7)(9+b) | | 6000=40w+w^2 | | 2(2c-3)-7=2c+5 | | a/4=32 | | 9x+1.5=19.5 |

Equations solver categories